Synthesis of 9,10-Diarylanthracenes via Mg(TMP)2·2LiCl-Mediated Benzyne Generation/[4+2] Cycloaddition and Deoxygenation of 9,10-Epoxyanthracene Intermediates - Miyamoto, Naoya; Nakazawa, Yuki; Nakamura, Takanori; Okano, Kentaro; Sato, Sota; Sun, Zhe; Isobe, Hiroyuki; Tokuyama, Hidetoshi (Synlett, 2018)
A new synthetic route to functionalized 9,10-diarylanthracenes has been developed. 9,10-Epoxyanthracene intermediates were prepared by [4+2] cycloaddition of 1,3-diarylisobenzofuran with a variety of functionalized benzyne intermediates, which were obtained by Mg(TMP)2·2LiCl-mediated benzyne generation. For the cleavage of the resultant 9,10-epoxyanthracene intermediates, we developed mild deoxygenation conditions using a combination of trifluoroacetic acid and Et3SiH. The utility of this sequence was demonstrated by application to the synthesis of 5,7,12,14-tetraphenylpentacene.
Keywords: anthracene; pentacene; arynes; cycloaddition; furanes; deoxygenation